Coxsackievirus A16: Epidemiology, diagnosis, and vaccine - Mao, Qunying (Landes Bioscience, 2014)
Coxsackievirus 16 (CA16) is one of the major pathogens associated with hand, foot, and mouth disease (HFMD) in infants and young children. In recent years, CA16 and human enterovirus 71 (EV71) have often circulated alternatively or together in the Western Pacific region, which has become an important public health problem in this region. HFMD caused by CA16 infection is generally thought to be mild and self-limiting. However, recently several severe and fatal cases involving CA16 have been reported. Studies have shown that co-infection with CA16 and EV71 can cause serious complications in the central nervous system (CNS) and increase the chance of genetic recombination, which may be responsible for the large HFMD outbreak in Mainland China in 2008. For these reasons, recent studies have focused on the virological characteristics of CA16 and the development of CA16-related diagnostic reagents and vaccines.